2004
DOI: 10.1016/j.febslet.2004.04.081
|View full text |Cite
|
Sign up to set email alerts
|

Poorer NF‐κB signaling by microfilariae in macrophages from BALB/c mice affects their ability to produce cytotoxic levels of nitric oxide to kill microfilariae

Abstract: Upon activation with microfilariae (mf), macrophages from C57Bl/6 mice showed higher nuclear factor-jB (NF-jB) but lower activating protein 1 DNA-binding activity as compared to BALB/c macrophages. The C57Bl/6 macrophages produced cytotoxic levels of nitric oxide (NO) to kill Setaria cervi mf as compared to BALB/c macrophages. Inhibition of the NF-jB signal by pyrrolidine dithiocarbamate (PDTC) blocked NO production and microfilaricidal activity of C57Bl/6 macrophages and inclusion of the exogenous NO generato… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
16
0

Year Published

2006
2006
2023
2023

Publication Types

Select...
8
1

Relationship

3
6

Authors

Journals

citations
Cited by 38 publications
(17 citation statements)
references
References 55 publications
1
16
0
Order By: Relevance
“…Therefore, it appears that NAC/GSH-OEt specifically activates SOCS1 that prevents p65 NF-kB from translocation to the nucleus without affecting c-rel and p50 NF-kB. As a result, p65-dependent TNF-a and iNOS genes (23)(24)(25)41) were not induced in these macrophages, whereas c-rel/c-rel or c-rel/p50-dependent genes like IL-12 (20) were induced.…”
Section: P38 Mapk Is Involved In the Gssg-mediated Regulation Of C-rementioning
confidence: 85%
See 1 more Smart Citation
“…Therefore, it appears that NAC/GSH-OEt specifically activates SOCS1 that prevents p65 NF-kB from translocation to the nucleus without affecting c-rel and p50 NF-kB. As a result, p65-dependent TNF-a and iNOS genes (23)(24)(25)41) were not induced in these macrophages, whereas c-rel/c-rel or c-rel/p50-dependent genes like IL-12 (20) were induced.…”
Section: P38 Mapk Is Involved In the Gssg-mediated Regulation Of C-rementioning
confidence: 85%
“…Because increased phosphorylation and degradation of IkBa was noticed at 3 mM NAC concentration (a situation with a higher intracellular GSH/GSSG ratio), it was expected that similar to c-rel (Fig. 3A), more p50 and p65 NF-kB would be available in the nucleus to start transcription of the NFkB-dependent genes like TNF-a and inducible NO synthase (iNOS) (23)(24)(25)41). However, we found that NAC at 3 mM concentration did not activate TNF-a (Fig.…”
Section: P38 Mapk Is Involved In the Gssg-mediated Regulation Of C-rementioning
confidence: 99%
“…Cytokine EIA-The levels of IL-10 and TNF-␣ cytokines were quantified by two-site sandwich EIA (BD Biosciences) as described earlier (35,37). Standard curve for these cytokines were obtained using the recombinant standard proteins provided by the manufacturer.…”
Section: Methodsmentioning
confidence: 99%
“…23 The RAW 264.7 macrophages were obtained from NCCS (National Centre for Cell Science, Pune, India) and maintained in Dulbecco minimal essential medium (DMEM; Invitrogen, Grand Island, NY) containing 10% fetal calf serum and antibiotics (DMEM-10). The macrophages were plated at a density of 3 ϫ 10 6 cells/mL and stimulated with a combination of 1 g/mL lipopolysaccharide Reprints: Sangita Mukhopadhyay, Centre for DNA Fingerprinting and Diagnostics, ECIL Rd, Nacharam, Hyderabad 500 076, Andhra Pradesh, India; e-mail: sangita@cdfd.org.in.…”
Section: Macrophage Stimulation Assaymentioning
confidence: 99%